2021
DOI: 10.1038/s41467-021-25689-y
|View full text |Cite
|
Sign up to set email alerts
|

A moisture-tolerant route to unprotected α/β-amino acid N-carboxyanhydrides and facile synthesis of hyperbranched polypeptides

Abstract: A great hurdle in the production of synthetic polypeptides lies in the access of N-carboxyanhydrides (NCA) monomers, which requires dry solvents, Schlenk line/gloveboxe, and protection of side-chain functional groups. Here we report a robust method for preparing unprotected NCA monomers in air and under moisture. The method employs epoxy compounds as ultra-fast scavengers of hydrogen chloride to allow assisted ring-closure and prevent NCA from acid-catalyzed decomposition under moist conditions. The broad scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 59 publications
0
64
0
Order By: Relevance
“…Highly pure ProNCA was prepared using a moisture-resistant method that our lab recently developed [ 40 ], which significantly simplified the conventional procedure that involves laborious workup. The application of this method also improved the yield to 72%, up from 30% reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Highly pure ProNCA was prepared using a moisture-resistant method that our lab recently developed [ 40 ], which significantly simplified the conventional procedure that involves laborious workup. The application of this method also improved the yield to 72%, up from 30% reported previously.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in 1964, Saito reported that free β-OH Thr NCA could be formed but polymerization attempts led to rearrangement to the 2-oxazolidinone derivative rather than the polypeptide . Recent work on free β-OH Thr NCA has also shown that epimerization of the α-carbon leads to diastereomers . Therefore, NCA studies have used various β-OH-protected Thrs including trimethylsilyl (TMS), , tert -butyl, benzyl (Bn), and diphenylphosphate as protecting or functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic polypeptides are protein-like polymers having precise control over α-helical and β-sheet conformations for wide range of applications in materials science and biomedical fields. Polypeptides are synthesized by ring-opening polymerization (ROP) of N -carboxyanhydride (NCA) monomers of l -amino acids by nucleophiles or base initiators, and in this process, secondary structures of the propagating polypeptide chains are rationalized as being a foremost deciding factor in determining the kinetics and building the high-molecular-weight polymers . α-Helical polypeptides render excellent solubility in the polymerization medium to speed up the ROP process and exhibit “livingness” to make extended block copolymer architectures .…”
Section: Introductionmentioning
confidence: 99%